System Vibration Control Using Linear Quadratic Regulator - M. Abdelrahman; G. Aryassov; M. Tamre; I. Penkov (International Journal of Applied Mechanics and Engineering, 2022)
Balancing a bipedal robot movement against external perturbations is considered a challenging and complex topic. This paper discusses how the vibration caused by external disturbance has been tackled by a Linear Quadratic Regulator, which aims to provide optimal control to the system. A simulation was conducted on MATLAB in order to prove the concept. Results have shown that the linear quadratic regulator was successful in stabilizing the system efficiently.